Pengembangan Aplikasi Berita Online Berbasis Android pada Website TANJUNGPINANG POS Menggunakan Android Studio - Kripto Kurnia Perkasa (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2019)
Tanjungpinang Pos is a National newspaper from Kepualaun Riau that hasbeen present for the people of Tanjungpinang city, almost every day this newspaperis present to accompany the public with news about the city of Tanjungpinang andother Riau territories, with technology development such as this Tanjungpinang Postnewspaper also opens a digital market with presenting a website for its news site,but the need for news is getting wider, with the increasing market for Androidsmartphone users, it is pushing to create an online Android-based news application.In the future, to present online news more widely with this application. Thisapplication works by connecting to the Tanjungpinang Pos news site, so that whenthe website updates the application the issue will also be updated. The application isnot needed to install this application, this application makes using Android Studiosoftware that will connect it to the Tanjungpinang Pos website, this application aimsto access Android users in accessing news through their smartphone, so users canonly install the application and will get news up to date every day.